2014
DOI: 10.1386/ajms.3.2.241_1
|View full text |Cite
|
Sign up to set email alerts
|

The nature of Arab public discourse: Social media and the ‘Arab Spring’

Abstract: This article focuses on the use and significance of social media in the Arab region, particularly among Arab journalists within the context of the events known as ‘the Arab Spring’. Besides describing the social media tools preferred by the public and by Arab media professionals, the article assesses the relative use and trust of new versus old media tools. The article also explores the relationship between the use of social media in the Arab region and the political and social uprisings in Tunisia, Libya, Eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In the aftermath of the Arab Spring revolutions in early 2011, teachers and political pundits have tried to determine the reasons and elements that brought about those movements' achievements or failures. While everyone has confronted its very own particular set of political, social, and monetary problems, a not unusual place thread that instructional observers have detected is the more and more not unusual place use of social media for functions of revolution (Al-Jenaibi, 2014).…”
Section: Regional Developments and Arab Springmentioning
confidence: 99%
“…In the aftermath of the Arab Spring revolutions in early 2011, teachers and political pundits have tried to determine the reasons and elements that brought about those movements' achievements or failures. While everyone has confronted its very own particular set of political, social, and monetary problems, a not unusual place thread that instructional observers have detected is the more and more not unusual place use of social media for functions of revolution (Al-Jenaibi, 2014).…”
Section: Regional Developments and Arab Springmentioning
confidence: 99%
“…The survey, aimed to get many comments and attitudes from students, was sent on the Ministry's Twitter and Facebook sites (Schools in UAE, 2014). Al-Jenaibi (2014) argued that the most well-known SN tools in the UAE are usually similar to those used in other counties in the Middle East, including Facebook, YouTube, Twitter, and others. UAE students are both generally skilled in the use of a variety of SN, and well aware of its possible moral and practical limitations.…”
Section: Sn In the Uaementioning
confidence: 99%
“…The Arab spring became a reference point in many discourses given the role it played in amplifying and accelerating regime changes in Tunisia, Egypt and Libya. Al-Jenaibi (2014) in a survey of respondents from the Arab region found that social media outlets complemented old media and served as a catalyst for the uprisings that have swept several Arab states in the Middle East. Social media was used to mobilize for rioting, street protests and violence in Hungary in 2006.…”
Section: Introductionmentioning
confidence: 99%